High-Growth Enterprises in times of COVID-19: An overview - Alexander Coad; Sofia Amaral-Garcia; Péter Bauer; Clemens Domnick; Péter Harasztosi; Rozália Pál; Mercedes Teruel (European Commission, Joint Research Centre (JRC), 2022)
This paper contributes to a fast-growing literature on the impact of COVID-19 on the business economy, by focusing on how a particular group of firms - High-Growth Enterprises (HGEs) have been affected by COVID-19 across several dimensions, such as investment expectations, investment priorities, employment decisions, and their post-COVID-19 green and digital transitions. Using the EIB Investment Survey (EIBIS) and relying on descriptive statistics and basic regressions, the results suggest that COVID-19 has had a significant impact on the investment expectations of HGEs, although they continue to invest slightly more than nonHGEs. Preliminary results suggest that HGEs appear to be more optimistic than non-HGEs in a variety of dimensions, such as optimism surrounding the use of digital technologies, and willingness to invest in climate mitigation and adaptation. However, our evidence shows that the HGEs in the 2020 survey wave have still been hit hard by the COVID-19 shock, compared to HGEs in previous years, which suggests that there may be a role for policy for supporting these valuable firms.
Keywords: 330; Innovative KMU; Coronavirus; Investitionsentscheidung; Unternehmenserfolg; EU-Staaten